Inefficiencies in the baseball labour market: An analysis of roster construction strategies of the Cleveland Guardians and the Tampa Bay Rays for 2022 MLB season. - Will Houslander (The Young Researcher)
In this study, a three-step method was used to assess one main question: How have the Cleveland Guardians and the Tampa Bay Rays found playoff success despite their low payrolls? First, this study found the correlation between 29 different baseball statistics and MLB teams win- ning percentages during the 2022 season. The correlation was found using Pearson’s correlation co-efficient, specifically looking for statistics with strong correlations with r-values > 0.6 or > -0.6. Ten statistics were found to have a strong correlation to winning percentage in 2022. Next, a log-linear regression analysis was used to analyze which of the strongly correlated metrics were the most undervalued in the baseball labour market. Lastly, step three discovered whether the Rays and the Guardians value the undervalued statistics identified in step two. The results of this study indicate that both the Guardians and the Rays found success through their strong pitching staffs.